Pengaruh Citra Diri terhadap Perilaku Hedonisme Lifestyle pada Mahasiswa Unismuh Makassar - Siti Syalwa Salsabila; Qalbi Aulia H.R; Nurwandayani Nurwandayani; Syawal Akhir; Lukman Ismail; Nasriah Nasriah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
Hedonistic lifestyles have become a common phenomenon among students, driven by technological advances, modernization and social pressure. This article aims to explain the relationship between a hedonistic lifestyle and self-image in students, the influencing factors, and the impact on their behavior. The research was carried out using the literature study method, by analyzing literature and related research results. A hedonic lifestyle is characterized by consumer behavior, a desire for social recognition, and a focus on personal pleasure. The main factors that influence this lifestyle include family upbringing, peer influence, and relationships with partners. The impact of hedonic behavior includes excessive spending on non-essential needs, dependence on social trends, and lack of awareness of financial management. Additionally, college students are often caught in a cycle of excessive consumption, driven by social media and online shopping trends. This research highlights the need for awareness of wise financial management and positive social influence to help students live more balanced lives.